2020
DOI: 10.1038/s41590-020-00813-0
|View full text |Cite
|
Sign up to set email alerts
|

A new neutrophil subset promotes CNS neuron survival and axon regeneration

Abstract: Transected axons typically fail to regenerate in the central nervous system (CNS), resulting in chronic neurological disability in individuals with traumatic brain or spinal cord injury, glaucoma and ischemic reperfusion injury of the eye. Although neuroinflammation is often depicted as detrimental, there is growing evidence that alternatively activated, reparative leukocyte subsets and their products can be deployed to improve neurological outcomes. In the current study we identify a unique granulocyte subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
164
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(180 citation statements)
references
References 48 publications
3
164
0
Order By: Relevance
“…Sas and colleagues recently described a novel neutrophil subpopulation that is capable of promoting nerve repair following acute injury. 1 Immunosuppressive leukocytes were first described in 1977, in which Kung demonstrated that myeloid cells expressing arginase 1 (Arg1) were capable of suppressing cytotoxic responses. 2 Over the last 40+ years, a growing body of evidence has attributed immunosuppressive or regenerative properties to subpopulations of myeloid cells that express Arg1 and the mannose receptor (CD206), coining the terms alternatively activated cells, unconventional cells, M2 macrophages and N2 neutrophils.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sas and colleagues recently described a novel neutrophil subpopulation that is capable of promoting nerve repair following acute injury. 1 Immunosuppressive leukocytes were first described in 1977, in which Kung demonstrated that myeloid cells expressing arginase 1 (Arg1) were capable of suppressing cytotoxic responses. 2 Over the last 40+ years, a growing body of evidence has attributed immunosuppressive or regenerative properties to subpopulations of myeloid cells that express Arg1 and the mannose receptor (CD206), coining the terms alternatively activated cells, unconventional cells, M2 macrophages and N2 neutrophils.…”
mentioning
confidence: 99%
“…1) and spinal cord injury. 1 Some questions remain unanswered. Clearly, the study examined only one human cell line, HL-60, while immunosuppressive Arg1 + primary human neutrophils have been isolated and described in several disease states 13,14 and in pregnancy.…”
mentioning
confidence: 99%
“…Auto-antibodies against type I interferons have been observed in patients with life-threatening cases of COVID-19 ( Bastard et al., 2020 ). Activated immune cell infiltration of the brain parenchyma may include, however, the Ly6G lo subset of neutrophil-like cells with the capacity to induce CNS neural regeneration ( Sas et al., 2020 ).…”
Section: Dysregulated Inflammatory Responses In Covid-19mentioning
confidence: 99%
“…Precision biomedicine technologies produce overgrowing quantities of information from of high throughput data from finer-grained biomedical samples reaching single-cell (Hwang et al, 2018 ) and subcellular (Grindberg et al, 2013 ) levels that allow to discover new cell types (Boldog et al, 2018 ; Gerovska and Araúzo-Bravo, 2019 ; Sas et al, 2020 ). This increasingly precise cell data render existing cell classification systems obsolete and create the demand for automatic comprehensive data-driven cell classification methods.…”
Section: Introductionmentioning
confidence: 99%